Cabozantinib plus docetaxel and prednisone in metastatic castration‐resistant prostate cancer. (23rd October 2020) - Madan, Ravi A.; Karzai, Fatima H.; Al Harthy, Munjid; Petrylak, Daniel P.; Kim, Joseph W.; Arlen, Philip M.; Rosner, Inger; Theoret, Marc R.; Cordes, Lisa; Bilusic, Marijo; Peer, Cody J.; Dawson, Nancy A.; et al.
Abstract : Objective: To evaluate the safety and efficacy of cabozantinib combined with docetaxel. Patients and Methods: This was a phase 1/2 multicentre study in patients with metastatic castration‐resistant prostate cancer (mCRPC). Docetaxel (75 mg/m 2 every 3 weeks with daily prednisone 10 mg) was combined with escalating doses of daily cabozantinib (20, 40 and 60 mg). Based on the results of the phase 1 study, the investigation was expanded into a randomized study of docetaxel with prednisone (hereafter 'docetaxel/prednisone') plus the maximum tolerated dose (MTD) of cabozantinib compared with docetaxel/prednisone alone. Results: A total of 44 men with mCRPC were enrolled in this phase 1/2 trial. An MTD of 40 mg cabozantinib plus docetaxel/prednisone was determined. Dose‐limiting toxicities were neutropenic fever and palmar‐plantar erythrodysesthesia, and there was one death attributable to a thromboembolic event. In addition, grade 3 or 4 myelosuppression, hypophosphataemia and neuropathy were seen in three or more patients. In the phase 1 study, the median time to progression (TTP) and overall survival (OS) time were 13.6 and 16.3 months, respectively. In the phase 2 study, which was terminated early because of poor accrual, the median TTP and OS favoured the combination ( n = 13) compared to docetaxel/prednisone alone ( n = 12; 21.0 vs 6.6 months; P = 0.035 and 23.8 vs 15.6 months; P = 0.072, respectively). Conclusion: Despite the limited number of patients in this study, preliminary data suggest that cabozantinib can be safely added to docetaxel/prednisone with possible enhanced efficacy.